A Qualitative Study of Physicians' Decision‐Making in Four US States With Abortion Bans - Lauren J. Shiman; Catherine E. W. Freeland; Diana Romero; Wendy Chavkin (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Background Physicians in various specialties practicing in states in the United States (US) with near‐total abortion bans are constrained in providing appropriate care. There is a lack of understanding about how these constraints affect care quality, especially in care provided to pregnant people outside of obstetric care. Methods The Medical Integrity Initiative study team conducted 32 in‐depth interviews with physicians currently or recently practicing in four states with near‐total abortion bans (Alabama, Idaho, Oklahoma, and Tennessee). Participants were practicing in emergency medicine, maternal‐fetal medicine, obstetrics, oncology, or reproductive endocrinology. Between July and October 2024, we conducted interviews via Zoom and then transcribed them. The analytic team conducted thematic analyses informed by grounded theory methodology. Analysts coded data in Dedoose using open coding followed by axial coding, then iteratively analyzed them. Results Participants shared experiences related to clinical decision‐making which comprised three themes: (1) physicians have lost capacity and security in making independent treatment decisions; (2) physicians are forced to compromise care quality when all medical options aren't permitted; and (3) some participants engaged in acts of resistance to uphold their integrity as physicians. Conclusions Physicians practicing in four states with near‐total abortion bans face profound ethical, legal, and emotional challenges that alter their approach to the provision of evidence‐based care. These findings contribute to understanding workforce attrition, physician burnout, and the status of care provision in states with restrictive abortion laws.